Analisis alih bahasa yang digunakan oleh Agnez Mo - Iman, Topan Rahmatul (Titian: Jurnal Ilmu Humaniora, 2022)
Abstract: Using language as a communication tool requires a relationship between people and society. This relationship is referred to as sociolinguistics. In Indonesia, many people speak more than one language. This phenomenon can be clearly observed in television talk shows, in which celebrities or public figures use code-switching. One celebrity who frequently switches from Bahasa Indonesia to English is Agnez Mo. This essay aims at investigating the identity Agnez Mo constructs using code-switching, and at examining the grammatical aspects in the production of code-switching. Regarding the data collection, as the study focuses on the analysis of the code-switching performed by Agnez Mo on the conversation with Deddy Corbursier (the host) on the Hitam Putih talk show on one of TV channels on YouTube was downloaded. The data collected were analyzed in five stages: listening to the recording, re-listening to the recording while transcribing the conversation, identifying the words that will be analyzed, analyzing the specific phenomenon, and checking the data. The data shows that she builds two different identities, one being multicultural identity and the other religiosity. Also, the data shows that Agnez Mo switches her language using the three types of code-switching: extrasentential, inter-sentential, and intra-sentential code-switching. Â Keywords: Analyzing, Identity, Code Switching